Low serum 25-hydroxyvitamin D status in the pathogenesis of stress fractures in military personnel: An evidenced link to support injury risk management - Armstrong, Richard A. (PLoS One, 2020)
Stress fractures are common amongst healthy military recruits and athletes. Reduced vitamin D availability, measured by serum 25-hydroxyvitamin D (25OHD) status, has been associated with stress fracture risk during the 32-week Royal Marines (RM) training programme. A gene-environment interaction study was undertaken to explore this relationship to inform specific injury risk mitigation strategies. Fifty-one males who developed a stress fracture during RM training (n = 9 in weeks 1–15; n = 42 in weeks 16–32) and 141 uninjured controls were genotyped for the vitamin D receptor (VDR) FokI polymorphism. Serum 25OHD was measured at the start, middle and end (weeks 1, 15 and 32) of training. Serum 25OHD concentration increased in controls between weeks 1–15 (61.8±29.1 to 72.6±28.8 nmol/L, p = 0.01). Recruits who fractured did not show this rise and had lower week-15 25OHD concentration (p = 0.01). Higher week-15 25OHD concentration was associated with reduced stress fracture risk (adjusted OR 0.55[0.32–0.96] per 1SD increase, p = 0.04): the greater the increase in 25OHD, the greater the protective effect (p = 0.01). The f-allele was over-represented in fracture cases compared with controls (p<0.05). Baseline 25OHD status interacted with VDR genotype: a higher level was associated with reduced fracture risk in f-allele carriers (adjusted OR 0.39[0.17–0.91], p = 0.01). Improved 25OHD status between weeks 1–15 had a greater protective effect in FF genotype individuals (adjusted OR 0.31[0.12–0.81] vs. 1.78[0.90–3.49], p<0.01). Stress fracture risk in RM recruits is impacted by the interaction of VDR genotype with vitamin D status. This further supports the role of low serum vitamin D concentrations in causing stress fractures, and hence prophylactic vitamin D supplementation as an injury risk mitigation strategy.